Representações, memórias e percepções de direitos humanos partilhadas por estudantes imigrantes haitianos: um estudo de caso no Cieja Perus/SP - Carvalho, Yuri Valladão (2023)
It is exposed that Human Rights are conceptualized as universal, inalienable and essential rights for the exercise of citizenship and the dignity of the being. Formally, such Rights are foreseen both in conventions, treaties, and international agreements. However, current society recreates its own perceptions of Human Rights and its normative social representations, as well as being able to influence the behavior of its individuals, making the universality of human rights complex. It is also known that Brazil has become a recipient of immigrants over the last few decades, especially Haitians who, when they land here, seek to adapt to a new reality in the face of the numerous violations of human rights present in their daily lives. Due to these acts of violence, memories about the theme are fixed in the social imaginary of these immigrants throughout their lives and can lead them to the said and unsaid, which remain hidden in their memories so as not to bring up all the violations experienced. The present work proposes the accomplishment of a qualitative research with theoretical reference in the theory of the social representations and of the theory of the central core with intention to know the social representations about human rights that have been shared by Haitian immigrants. It was also proposed, supported by Michael Pollak, to understand the said and unspoken caught in the memories of these immigrants about the Human Rights that have been experienced throughout their lives. It was possible to identify the existence of a consolidated knowledge on the part of these immigrants about human rights that are commonly learned in Haiti, but which were in fact fixed in Brazil. Interpretations of human rights vary according to the thinking being directed: human rights in Brazil or human rights in Haiti? It was also found that these immigrants anchor human rights in the social crisis, in the social normative aspects and in the existing difficulties rooted in their history as Haitian citizens, precisely because of the lack and disrespect of these basic rights for the development of any human being.